Lobaplatin Induces Pyroptosis in Cervical Cancer Cells via the Caspase-3/GSDME Pathway - Chen, Jie; Ge, Lili; Shi, Xiaoyan; Liu, Juan; Ruan, Hongjie; Heng, Dou; Ye, Chunping (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Increasing evidence shows that GSDME is involved in tumor chemotherapy. Lobaplatin is an important chemotherapy drug for the treatment of cervical cancer. However, the exact mechanism of lobaplatin in the treatment of cervical cancer remains unclear. Objective: In this study, whether GSDME is a new mechanism of lobaplatin in the treatment of cervical cancer has been explored. Methods: Cell pyroptosis was measured by Cell Counting Kit-8 and flow cytometry analyses. Western blot analysis was used to check proteins expression. Results: The cell viability was significantly decreased by lobaplatin treatment. Compared with the control group, the percentage of pyroptosis (PI and Annexin-V double-positive cells) increased after lobaplatin treatment. In addition, lobaplatin induced caspase-3 activation and GSDME cleavage. z-DEVD, a specific inhibitor of caspase-3, reduced lobaplatin-mediated GSDME cleavage and concurrently inhibited pyroptosis. More importantly, GSDME deficiency obviously reduced lobaplatin-induced pyroptosis. Conclusion: These data demonstrate that caspase-3/GSDME axis contributed to the lobaplatin-mediated pyroptosis in cervical cancer cells. This finding indicates that GSDME-mediated pyroptosis is a new mechanism for lobaplatin to kill tumor cells and suggests that the caspase-3/GSDME pathway offers new insights into cancer chemotherapy.
Keywords: lobaplatin